ARCHIVE What is a personal archive? How can it be shared and performed? - Cristina Ísabel Agueda 2001- (2024)
In this essay I will discuss and reflect on the process and performance of my work “ARCHIVE”. “ARCHIVE” was my individual graduation project in my final year of my Bachelor in Arts studies in Contemporary Dance Practices at the Iceland University of the Arts. Furthermore I will discuss the reason for my research and interest in archives, mixing mediums, identities, inspirations and diasporas. I will discuss my fascination with identities and archives and how I can possibly create a performative shared archive. I analyse my research, work and the broader concept of archives and identities. For this piece I collaborated with different artists in a form of multidisciplinary practice, allowing myself to become familiar with that method. I additionally worked solo, mostly physically in the studio using improvisation influenced by my memory and research.